P541 Introduction of high-flow nasal cannula oxygen in bronchiolitis management: a UK district general hospital perspective. (June 2019) - Maduemem, Kene; Sand, Laura; Chingale, Amol
Abstract : Background/aim: High-flow nasal cannula oxygen (HFNCO) has becoming increasingly used as a respiratory support in children with bronchiolitis. We aimed to evaluate the clinical characteristics, course and outcome of infants on HFNCO since its introduction in a DGH. Methods: This was a single-centre retrospective study of infants with clinical diagnosis of bronchiolitis on high-flow nasal cannula oxygen between September 2016 and January 2019. The clinical characteristics of these infants were evaluated. Their clinical course during therapy and outcome were analysed. Results: Twenty-two infants with bronchiolitis received HFNCO therapy over the study period. The age of the infants ranged between 1 week and 11.9 months. Comorbidities included prematurity, chronic lung disease, cystic fibrosis and trisomy 21. The commonest indications for its use were severe respiratory distress and pCO2 greater than 7.5 kPa. Chest radiograph and blood gas analysis were performed in all patients prior to commencement. The median start and maximum flow rates were 1.55 (range: 0.8–3.7) and 1.75 (range: 1–3.7) L/kg/min respectively. The mean time of improvement in work of breathing and heart rate was 2.06 (SD. 0.81) hours. The median length of therapy was 3.2 (range: 0.25–9.4) days. Treatment failure was recorded in 27% of cases; with transfer to tertiary centre. At least a comorbidity was present in 83% of treatment failure cases. All but one of the treatment failures were intubated. There were no adverse events or mortality in the study group. Conclusions: HFNCO has shown significant benefit in the management of moderately severe bronchiolitis since its introduction in this DGH. It can be safely applied in the emergency department or on the general paediatric wards. Infants with comorbidities presenting with bronchiolitis may require early escalation to HFNCO to reduce treatment failure.